2013
DOI: 10.1038/srep01457
|View full text |Cite
|
Sign up to set email alerts
|

Red coral extinction risk enhanced by ocean acidification

Abstract: The red coral Corallium rubrum is a habitat-forming species with a prominent and structural role in mesophotic habitats, which sustains biodiversity hotspots. This precious coral is threatened by both over-exploitation and temperature driven mass mortality events. We report here that biocalcification, growth rates and polyps' (feeding) activity of Corallium rubrum are significantly reduced at pCO2 scenarios predicted for the end of this century (0.2 pH decrease). Since C. rubrum is a long-living species (>200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 49 publications
(69 reference statements)
5
66
0
1
Order By: Relevance
“…For example, nutrients produced during the re-mineralization of organic matter at the deep seafloor are ultimately used by phytoplankton to produce organic matter that fuels secondary production. At the same time, organic-matter degradation and re-mineralisation contribute to carbon biogeochemical cycling in the ocean, and help to buffer the ocean against pH changes and the effects of ocean acidification Wenzhöfer et al, 2001;Cerrano et al, 2013). The health and sustainable functioning of the planet are therefore highly dependent on the deep sea (defined here as > 200 m), which accounts for more than 95% of the volume of the Earth's oceans.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nutrients produced during the re-mineralization of organic matter at the deep seafloor are ultimately used by phytoplankton to produce organic matter that fuels secondary production. At the same time, organic-matter degradation and re-mineralisation contribute to carbon biogeochemical cycling in the ocean, and help to buffer the ocean against pH changes and the effects of ocean acidification Wenzhöfer et al, 2001;Cerrano et al, 2013). The health and sustainable functioning of the planet are therefore highly dependent on the deep sea (defined here as > 200 m), which accounts for more than 95% of the volume of the Earth's oceans.…”
Section: Introductionmentioning
confidence: 99%
“…The main threat to the red coral is intensive historical harvesting, which causes an overall shift in the population structure, resulting in a decrease in both biomass and colony size171819. Climate warming and the potential effects of ocean acidification are also major threats affecting populations12202122. It has been demonstrated that a decrease in the abundance of habitat-forming species leads to a rapid fragmentation in community structure and a loss of species benefiting from the structural complexity these species provide23242526.…”
mentioning
confidence: 99%
“…However, the most dominant observation is a loss in calcification rate or alteration of calcification structure with increasing OA conditions. This can be observed for temperate and polar species living in the areas most susceptible to OA Fabry et al 2008;Comeau et al 2012;Hoppe et al 2011;Cerrano et al 2013). Many studies on tropical calcifiers, such as corals, calcifying algae, molluscs, echinoderms, and crustaceans, indicate similar effects of OA.…”
Section: Calcificationmentioning
confidence: 84%